The Shift in Gender Roles in Amy Tan’s 'The Joy Luck Club' and Khaled Hosseini’s 'The Kite Runner' - Mujad Didien Afandi (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2018)
The unfair gender roles under patriarchal system are constructed to preserve gender inequality between men and women. Gender role practices extend gradually to maintain the male hegemony to make women powerless because female traditional gender roles (femininities) create dependency to men. Men are assigned to masculinities equipped with power, whereas women are ascribed to femininities to set boundaries that limit their movement. Yet, the increase of female awareness of gender equality has changed this situation. Gender roles are gradually shifting from traditional to modern as the opportunities to receive education and job open widely to develop women's roles that enable them to give financial contribution to the family. This study was purposed to analyze the shift in gender roles in 'The Joy Luck Club' and 'The Kite Runner'. This study used qualitative design in which Chinese traditional gender roles were described using Confucian perspective, whereas Afghan traditional gender roles were exposed in Islamic perspective. Moreover, Karl Marx's conflict theory was used to analyze the shift in gender roles in both novels. The results of study found that the construction of traditional gender roles in both China and Afghanistan was influenced mostly by patriarchy which perceives men as more superior than women. However, the dynamic changes of gender roles, especially femininities, supported by the increase of female education and occupation provide women with more power to achieve development. Further studies are encouraged to analyze other gender roles which have not discussed in this study.